New records of tardigrades from Mexico with the description of Paramacrobiotus puma sp. nov. (Eutardigrada: Macrobiotidae) - Daniel López-Sandoval; Griselda Montiel-Parra; Tila M. Pérez (Revista Mexicana de Biodiversidad)
Five samples of mosses and 2 samples of lichens were collected within the Cantera Oriente, in southern Mexico City. In total, 110 tardigrades and 27 eggs, belonging to 2 orders (Apochela and Parachela), 4 families (Milnesiidae, Hypsibiidae, Macrobiotidae, and Ramazzottiidae), 6 genera (Milnesium, Hypsibius, Notahypsibius, Minibiotus, Paramacrobiotus, and Ramazzottius) and 9 species were recorded. Milnesium longiungue Tumanov, 2006, Notahypsibius pallidoides Pilato, Kiosya, Lisi, Inshina and Biserov, 2011 and Paramacrobiotus gadabouti Kayastha, Stec, Mioduchowska and Kaczmarek, 2023, represent new records for Mexico. The species Paramacrobiotus puma sp. nov. is new to science and its description is provided and supported by phase contrast light microscopy (PCM), scanning electron microscopy (SEM) and analysis of nucleotide sequences of 3 nuclear and 1 mitochondrial markers. The new records increase the diversity of the phylum to 87 species in the country.